Parent Perspectives on the Acceptability and Impact of a Telehealth Social Skills Intervention for Adolescents with Neurofibromatosis Type 1 - (:unkn) unknown (My University, 2024)
Research has shown that children and adolescents with neurofibromatosis type 1 (NF1) are at increased risk for social difficulties in comparison to unaffected peers (Huijbregts et al., 2015). Research has described many negative outcomes for unaffected children with social functioning challenges such as loneliness, aggression, conduct problems, substance abuse, and mental health difficulties (Caemmerer & Keith, 2015; Woodward & Fergusson, 2000). The current literature on social skill interventions in the NF1 population is slim. Our research group (Glad et al., 2023) has conducted a preliminary pilot study to examine social skill improvement in the NF1 population with implementation of the telehealth version of the Program for the Enrichment and Educational of Relational Skills (PEERS) curriculum – an intervention designed to improve social skill knowledge and functioning through training of caregivers and affected participants (Laugeson & Frankel, 2012). As part of the pilot study an anonymous questionnaire was administered to caregivers to collect data on patient satisfaction, curriculum review, and quality improvement in the form of rating scales and free-response questions. Analysis of the qualitative and quantitative data from the anonymous questionnaire support the PEERS curriculum as an acceptable intervention to address the social needs of children with NF1 and indicated that the approach yielded improvement in social functioning from the parental perspective. The findings also underscore the importance of recognizing and addressing the subtleties of social difficulties in NF1, which may not always be captured by norm-referenced measures.